REDUCTION OF ST SEGMENT ELEVATION IN DIABETIC PATIENTS WITH MYOCARDIAL INFARCTION AFTER THROMBOLYTIC THERAPY - Syed, Uneeba (Journal of Ayub Medical College Abbottabad, 2017)
Background: Acute coronary artery disease (CAD) is one of the main cause of death in today’s world. Myocardial infarction (MI) tends to be more common among diabetic patients. One of the most effective and used (in our settings) methods of resolution of MI is administration of streptokinase (SK). This study was conducted with the aim to determine the efficacy of thrombolytic therapy in reduction of ST segment elevation in acute MI patients presenting with diabetes. Methods: A descriptive case series with selection of 130 patients through non-probability purposive sampling was conducted at the Medical Departments of Services Hospital Lahore. The study was completed in 6 Months. Patients 18-80 years of age having either gender diagnosed with confirmed acute myocardial infarction were included in this study. All patients were then injected with streptokinase 1.5 mu. Pre and Post SK ECGs were done and ST segment elevation measured also measuring reduction of ST segment. Results: The mean age of the patients was noted as 54.42±8.80 years. There were 62.31% males. Mean reduction in ST-segment elevation of the patients was noted as 58.53±26.01. The efficacy was achieved in 47.7% patients. Conclusion: It is concluded that SK can be effective in almost half of diabetic patients with myocardial infarction. Keywords: Coronary Artery Disease; Myocardial Infarction; Streptokinase; ST segment reduction